2020
DOI: 10.21037/jtd.2020.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Management of anastomotic leaks after esophagectomy and gastric pull-up

Abstract: Anastomotic leak is one of the most feared complications of esophagectomy, leading to prolonged hospital stay, increased postoperative mortality, and additional cost both to the patient and the hospital. Historically, anastomotic leaks have been treated with several techniques including conservative measures, percutaneous or operative drainage, primary surgical repair with buttressing, T-tube drainage, or excision of the esophageal replacement conduit with end esophagostomy. With advances in treatment modaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
(60 reference statements)
0
18
0
1
Order By: Relevance
“…Severity of anastomotic leaks is important to distinguish as major leaks are not only associated with septic sequelae but are also associated with peritonitis, wound infections, atrial fibrillation, pneumonia, and respiratory failure. 16 Given the common occurrence and poor prognosis of anastomotic leaks, extensive research has been performed to determine risk factors and surgical techniques to mitigate them. However, there remains variation in literature regarding systemic factors associated with anastomotic leaks.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of anastomotic leaks is important to distinguish as major leaks are not only associated with septic sequelae but are also associated with peritonitis, wound infections, atrial fibrillation, pneumonia, and respiratory failure. 16 Given the common occurrence and poor prognosis of anastomotic leaks, extensive research has been performed to determine risk factors and surgical techniques to mitigate them. However, there remains variation in literature regarding systemic factors associated with anastomotic leaks.…”
Section: Discussionmentioning
confidence: 99%
“…The management of anastomotic leaks hinges on several factors, including the overall clinical status of the patient, presence of [multi]organ failure, spread or presence of infectious complications such as abscesses or mediastinitis, and viability of the tissue at the anastomosis, and can vary from conservative observation, primarily treated with antibiotics, to percutaneous drainage, and finally, surgery, pending the above factors. 14 Endoluminal stenting is a viable option for intrathoracic leaks in select patients, particularly those with contained leaks without broad mediastinal spread (Figure 1). The stent permits a barrier of protection for the healing esophageal mucosa and is coupled with appropriate antibiotic therapy, in addition to serial contrast examination approximately every 2 to 4 weeks to assess healing of the leak.…”
Section: Anastomotic Leaksmentioning
confidence: 99%
“…52 The growing burden of esophageal cancer in older adults will necessitate comparative effectiveness research to elucidate optimal treatment strategies for this large and medically complex population that is chronically underrepresented in clinical trials. [56][57][58][59][60][61][62][63] Due to the complexity and invasiveness of the procedure, the overall operative mortality rate is 4%, though low-volume centers have been associated with rates as high as 20%. 64,65 An analysis of Medicare patients with non-metastatic cancers who received esophagectomy reported that 30% of patients had a hospitalization or adverse event within two months of the procedure and 4% of patients died within this short-term window.…”
Section: Extent Of Tumor Invasionmentioning
confidence: 99%